2016
DOI: 10.1007/s11154-016-9365-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the modification of taste and food preferences following bariatric surgery

Abstract: There is a large body of evidence indicating that bariatric surgery provides durable weight loss and health benefits to patients who are obese and have comorbidities such as type 2 diabetes (T2D). However, there are still many questions related to mechanisms of metabolic improvement, predictors of success/failure, and long term consequences, which need to be answered. More recently, there has been a particular interest in the modulation of taste and food preferences that occurs after bariatric surgery and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 136 publications
(215 reference statements)
1
11
0
1
Order By: Relevance
“…In humans taste is an important factor governing eating behaviour as it contributes to food preference, and it is thought that it modulates appetite and caloric intake [1]. Obese patients report higher enjoyment for sweetness compared with normal weight subjects [2].…”
Section: The Role Of Tastementioning
confidence: 99%
“…In humans taste is an important factor governing eating behaviour as it contributes to food preference, and it is thought that it modulates appetite and caloric intake [1]. Obese patients report higher enjoyment for sweetness compared with normal weight subjects [2].…”
Section: The Role Of Tastementioning
confidence: 99%
“…Bariatric surgery seems to reverse these obesity-related alterations in taste perception (7)(8)(9)(10). However, controversy exists (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Several review articles have highlighted human studies of changes in preference for energy-dense foods following bariatric surgery [19,21,22]. Some studies utilize reported food intake (e.g., dietary recall, food frequency surveys) to assess changes in food preference across bariatric surgery [19].…”
Section: Introductionmentioning
confidence: 99%